2018
DOI: 10.1111/dgd.12571
|View full text |Cite
|
Sign up to set email alerts
|

Experience‐dependent transcriptional regulation in juvenile brain development

Abstract: During brain development, once primary neural networks are formed, they are largely sculpted by environmental stimuli. The juvenile brain has a unique time window termed the critical period, in which neuronal circuits are remodeled by experience. Accumulating evidence indicates that abnormal rewiring of circuits in early life contributes to various neurodevelopmental disorders at later stages of life. Recent studies implicate two important aspects for activation of the critical period, both of which are experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 96 publications
(152 reference statements)
0
5
0
Order By: Relevance
“…Pellis et al (2023) noted that juvenile play behavior in rats promotes increased behavioral skill and social competency during adulthood, and suggested that a general benefit of play may be to refine or improve skills and behaviors that can be applied adaptively across a variety of social and nonsocial contexts. Various aspects of brain development exhibit plasticity during neonatal and juvenile periods, and a range of experiences after birth can direct elements of neural and behavioral development (Johnson, 2001;Stiles and Jernigan, 2010;Kolb and Gibb, 2011;Sakai and Sugiyama, 2018). Various brain regions help to modulate the expression of play behavior in mammals (Pellis and Iwaniuk, 2004;Siviy, 2016;Achterberg and Vanderschuren, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Pellis et al (2023) noted that juvenile play behavior in rats promotes increased behavioral skill and social competency during adulthood, and suggested that a general benefit of play may be to refine or improve skills and behaviors that can be applied adaptively across a variety of social and nonsocial contexts. Various aspects of brain development exhibit plasticity during neonatal and juvenile periods, and a range of experiences after birth can direct elements of neural and behavioral development (Johnson, 2001;Stiles and Jernigan, 2010;Kolb and Gibb, 2011;Sakai and Sugiyama, 2018). Various brain regions help to modulate the expression of play behavior in mammals (Pellis and Iwaniuk, 2004;Siviy, 2016;Achterberg and Vanderschuren, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Various brain regions help to modulate the expression of play behavior in mammals (Pellis and Iwaniuk 2004;Siviy 2016;Vanderschuren et al 2016). Moreover, experiences after birth can play an important role in directing specific aspects of neural and behavioral development in mammals (Johnson 2001;Stiles and Jernigan 2010;Sakai and Sugiyama 2018). Pellis et al (2010Pellis et al ( , 2014 suggested that social play behavior refines the control that the prefrontal cortex has over other brain regions, facilitating more nuanced neural responses and more adaptable behavior later in life.…”
Section: Discussionmentioning
confidence: 99%
“…17 A related issue is that perturbing OTX2 in the adult VTA may not be effective because OTX2 activity may only be required during a specific developmental window 17 or critical period, which is consistent with a known role for OTX2 in critical period plasticity in the visual system. 37,38 Finally, it is possible that OTX2 in the VTA just doesn't play a role in ethanol intake. Otx2 is expressed in select regions of the CNS and could presumably be involved in binge-like ethanol drinking through its transcriptional activity in those regions.…”
Section: Discussionmentioning
confidence: 99%